MAKTABGACHA YOSHDAGI BOLALARNI MA’NAVIY-AXLOQIY TARBIYALASHDA TARBIYACHINING O‘RNI - Usarova Muborak Xabibulla qizi; Abduraxmanova Matluba Kamoliddin qizi (TADQIQOTLAR, 2025)
Abstract: In this article, raising children as well-rounded individuals is considered one of the most important tasks of the education system. Spiritual and moral education plays an important role in the formation of a child's personality, social relationships, and cultural behavior. In particular, the preschool period is one of the most important stages in human life, and the spiritual values and moral standards formed during this period affect the child's future personal and social success.